Manage comfort preferences conflicts using a multi-agent system in an adaptive environment system - Oliveira, Pedro Filipe (2021)
Managing comfort preferences conflicts of the different users and locals on an IoT adaptive system is a actual problem, this paper proposes a protocol and hierarchical rules to develop a multi-agent system to achieve a Adaptive Environment System that solves the management of conflicts in an autonomous way for the users and interdependent of the user schedules and routines.